A “citation classics” analysis of articles in contemporary small enterprise research - Ratnatunga, Janek; Romano, Claudio (Journal of Business Venturing, 1997)
This research study has two distinct steps: (1) a quantitative analysis to identify the citation classics in contemporary small enterprise research (CSER) and (2) a more qualitative discussion of the contributions of these classical articles. The motivation of the study is to reveal the evolution of thought in the relatively new field of entrepreneurship research. CSER is defined as all main articles published during 1986–1992 in the Journal of Small Business Management, International Small Business Journal, Entrepreneurship: Theory and Practice, Journal of Business Venturing, Small Business Economics, and the Asia Pacific International Management Forum. The resultant analysis encompasses 725 articles and approximately 16,720 of their citations. The quantitative analysis revealed that the source journals have been responsible for the publication of 35% of the most cited articles during the 18-year period of analysis, with each subperiod increasing the percentage of citations from these source journals. The qualitative analysis of the citation classics articles indicated that more than 50% of CSER articles are well grounded in observational and contemplative theory building with a view to developing convergent theories that provide an overall understanding of the entrepreneurial process. This is similar to the pattern of citations in other emerging fields. This citation classics analysis reveals a number of points. First, the main topic areas of inquiry in the citations classics were: personal characteristics of entrepreneurs, financing and venture capital, and entrepreneurial climate and its relation to society, and strategy and growth. Of these, the personal characteristics of entrepreneurs was a consistent topic over the entire CSER period. However, the general diversity of topic areas provides some empirical support for the “garbage can model” synthesized from earlier studies of emerging fields in which diversity in topic areas has been characterized as a loose collection of ideas rather than a coherent structure with a shared intellectual paradigm. A similar characterization can be made of the entrepreneurial research during the CSER period. Second, the most evident methodology was observational and contemplative theory building, although empirically based survey techniques were gaining favor in the latter two periods. Third, the dominant objective of most research was to improve the understanding of small enterprise theory. This dominance of the theory building literature has also been observed in other citation studies of emerging fields. Fourth, it appears that many of the most cited articles have drawn upon the literature of related and nonrelated disciplines. Many of these articles have been exploratory in nature and have attempted to rationalize concepts and variables used in small enterprise research. Finally, CSER citation classics have been impacted only by Journal of Business Venturing, Journal of Small Business Management, and Entrepreneurship: Theory and Practice among the source journals.